Energy reduction measures in office buildings converging to NZEB: three case studies - Hormigo, Joao (2018)
The present paper is mainly focused on the energy performance of three office buildings [1], [2], [3] with different floor areas and ages , located in different geographical provinces of Portugal: Coimbra , Castelo Branco and Setúbal. On a first stage the study consisted on the characterization of the real energy consumption of each building, and the energy consumption partition between HVAC, lighting and equipment. On a second stage several proposals for energy consumption improvement were simulated for each building using Energy Plus/Sketch up models. The simulation models have considered changes in some construction systems and additionally the installation for solar energy generation systems in the buildings. Therefore the best approaches for the reduction of energy consumption in each buildings were obtained. The analysis of results and related conclusions were focused not only in effective reduction of energy consumption but also in the relationship between the benefits resulting of the implementation of each proposal and respective costs. For each proposal the return on the investment period is also presented. Based on real cases the present paper pretends to emphasise the need to implemente the reduction of energy consumption in buildings and specifically emphasises that some reductions can be developed without stopping the regular operation of the buildings. Some interventions are attractive regarding the factor cost/benefit.